PHYTOCHEMICAL SCREENING OF BIOACTIVE COMPOUNDS FROM DIFFERENT POPULATIONS OF HIPPOPHAE RHAMNOIDES L. GROWING IN KARGIL DISTRICT (J & K, INDIA) - DEEPAK GUPTA; VEENU KAUL (International Journal of Pharma and Bio Sciences, 2012)
Species of genus Hippophae commonly called Sea buckthorn grow in more than 30 countries of the world. Belonging to the family of Elaeagnaceae, each and every part of the plant is a source of about 190 bioactive substances which include many antioxidants. Different populations of Hippophae rhamnoides L. growing in Kargil district of Ladakh region of J&K (India) were subjected to the quantification of total phenolic, carotenoid and chlorophyll (a & b) contents in male and female plants. The total phenols across populations ranged from 54.4 to 86.4 mg/0.25g GAE. Chlorophylls and carotenoids varied from 7.74 to 45.02 and, between 0.0170 and 0.0399 mM/0.5g respectively. Comparative evaluations made in male and female plants at inter- and intra- population levels reveal higher contents of almost all these antioxidants in the male sex. Some populations like Barootsog, Andoo, Kanoor and Mingee were found to be promising.